Growing in the Dark Warmth: The Case of Amazonian Fish Colossoma macropomum - Amanajás, Renan D.; Silva, Jhonatan M.; Val, Adalberto L. (Frontiers in Marine Science, 2018)
Photoperiod is considered an important synchronizer of biological activities and endocrine pathways, including growth. As ectotherms, fish have many physiological functions controlled by the photoperiod. However, the combined effects of photoperiod and temperature should be clarified, particularly for tropical fish living near their upper thermal limit, as is the case of Amazonian fish. The central aim of this study was to evaluate the combined effect of photoperiod and temperature on growth and physiological aspects of tambaqui (Colossoma macropomum). Juveniles of tambaqui were distributed in 70 L tank, following a factorial design that included three photoperiods (light 0 h: darkness 24 h; light 12 h: darkness 12 h; and light 18 h: darkness 6 h) associated with three temperatures (26, 29 and 32 oC). They were maintained under these conditions for two months. Fish reared in the dark at 29 and 32 oC showed better performance compared to fish reared under extended light conditions at all temperatures. Among physiological responses, it has been observed that blood parameters tend to be disturbed with increasing temperature and that extended light conditions at low temperatures caused similar effects on the analyzed fish, suggesting blood hemoconcentration. Fish under extended light conditions showed an increase in glucose, cortisol, cholesterol and total proteins, indicating additional physiological disturbances. In conclusion, our study shows that, unlike marine and temperate fish, C. macropomum, a fish species endemic to the Amazon, grows better in warmth dark, showing no significant physiological disturbances, similar to observations described for wild animals of this species. Our results support that changes in fish growth occur in response to environmental conditions. Therefore, fish species from freshwater, estuarine and marine environments, must be specifically analyzed regarding the combination effects of photoperiod and temperature.